Analisis Pengaruh Pengungkapan CSR dan EPS terhadap Nilai Perusahaan dengan Size sebagai Variabel Moderasi - Marsya Salsabila Gartiwa; Leni Nur Pratiwi; Endang Hatma Juniwati; Radia Purbayati (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this study is to examine the impact of CSR disclosure and EPS on firm value in mining companies listed on the ISSI, with size acting as a moderating variable. This is based on the fluctuating firm value, the increase in conflicts related to CSR, and the difference in firm value proxied by Tobin's Q and EPS. A purposive sampling technique was used to obtain the number of research samples, with 15 mining companies consistently registered at ISSI for the 2016-2020 period. This is a quantitative study that employs multiple regression analysis with panel data and moderated regression analysis with a statistical data processing application. According to the results, CSR disclosure has a negative and insignificant effect, whereas EPS has a positive and significant effect on firm value. Simultaneously, CSR and EPS disclosures have a significant effect, and the size variable is unable to moderate this effect.